Rural livelihood and food security - M.H. Wani; S.H. Baba (New Delhi : New India Publishing Agency, 2012)
The world food situation is currently being redefined by new driving forces like income growth, climate change, high energy prices, globalization, and urbanization. About 73 million people will be added to the world,s population every year between 1995 and 2020. This population growth will occur in the cities of the developing world while its rural population is expected to increase by less than 300 million during this period. Changes in food availability, raising commodity prices, and new retailer-consumer linkages have crucial implications for the livelihoods of poor and food-insecure people. Meeting the food needs of a growing and urbanizing population with rising income will have profound implications on the world,s agricultural production and trading systems in coming decade.The technological break through and government intervention under Green Revolution era has alleviated Indian agricultural economy out of the low productivity trap and we have shifted from food shortage and imports to self-sufficiency and export. However, the evolving global context of agriculture coupled with steady increase in population has set major challenges to our development planning.
Include reference.
Keywords: Food security-India; Rural livelihood-India